LEGAL AND ORGANISATIONAL SPECIFICS OF EXECUTIVE AUTHORITY LAW-MAKING PLANNING ABROAD (THE CASE STUDY OF THE SOCIALIST REPUBLIC OF VIETNAM) - Nguyen, Xuan Bien; Nguyen, Xuan Le Cuong; Pyvovar, Iryna V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
This article analyses the laws of the Socialistic Republic of Vietnam in the context of defining the specifics of the involvement of public administration bodies (namely, the central executive authorities) in the process of public law-making planning in general and departmental law-making planning in particular. It contains positive aspects of foreign experience, which should be realised in the Ukrainian law-making process.